Sistem Pendukung Keputusan Evaluasi Problematika Pendampingan Pembelajaran Daring dengan Algoritma C4.5 - Ramadhan, Abiyyu (Jurnal Sistim Informasi dan Teknologi, 2022)
The Covid-19 pandemic has had an impact on many parties, this condition has penetrated the world of education, the central government to the regional level provides policies to close all educational institutions. However, the problem is currently, education in Indonesia and even the world is faced with a situation that makes teachers and students master distance or online learning, especially during this Covid-19 pandemic. In this study, the use of the C4.5 algorithm method used questionnaire data distributed and filled in by teachers who teach at SDN 14 ATTS Bukittinggi City which contains questions, namely the teacher's name, student name, subject, class, UTS and UAS scores, student obstacles during online learning such as students not having devices, students arriving late, uncooperative students. With this research, students at SDN 14 ATTS will get an appropriate learning method for each subject, so that students can absorb knowledge to the maximum and have satisfactory results in online learning. A Decision Support System using the C4.5 Algorithm can be applied in determining the right method for online learning for students so that they can better understand the material provided by the teacher and get satisfactory results in online learning.